Bringing economies of integration into the costing of groupage freight - Christian Brabänder; Maximilian Braun (Journal of Revenue and Pricing Management, 2020)
The purpose of this paper is to develop a novel calculation scheme for the costs of distribution per shipment according to a cost-by-cause principle. We propose to estimate the full costs of distribution routes excluding and including a new consignor. Then, we estimate the marginal costs per shipment and per consignor. The contributions of this paper are (1) a comprehensive list of drivers of Economies of Integration and (2) a calculation scheme, how to estimate true marginal cost of new consignors. Practitioners may deploy the method and insights of this paper for tariff design, negotiations, consignor acquisition, and also demarketing.
Keywords: 330; Groupage freight; LTL; Tariffs; Pricing of transportation services; Discounts; Shipment structure analysis